Medicinal Plants as Potential New Target Drugs in Endocrine Disorders- Review Article - Shirin HASANI-RANJBAR; Bagher LARIJANI (Tehran University of Medical Sciences, 2015)
Noncommunicable diseases pose a real threat to and their incidence is forecast to increase in both developed and developing countries; and, diabetes, obesity, and related complications are predicted to pose a great burden on health care systems all across the world. However, current used conventional medications and surgical interventions fall short of effectively controlling the rampant spread of obesity and diabetes. Moreover, as the world population grows older, increases the need for more effectively controlling old-age diseases such as obesity and diabetes. It is clear that many traditional plants are used for treatment of diseases in Iran and throughout the world as adjuncts to conventional therapy. This work aimed to present current science on the efficacy and safety of medicinal plants useful in diabetes mellitus, obesity, hyperlipidemia, hyper prolacrinemia and antioxidant effects by reviewing all human and some animal studies. Amongst reviewed studies, some natural products were found effective in the treatment of these metabolic disorders that deserve further works to isolate and characterization of their constituents to reach novel therapeutic agents. The findings of the current study demonstrated that some medicinal plants are effective in the treatment of different metabolic and endocrine disorders. For example Citrulluscolocynthis, Silybummarianum, Psyllium, Teucriumpolium, pomegranate, ginseng, Aloe vera and fenugreek decreased blood glucose significantly. Moreover, a variety of herbal supplements were found to be effective in the management of obesity such as ephedra, cissusquadrangularis, ginseng, bitter melon (Momordicacharantia), and zingiber.   Keywords: Medicinal plants, Diabetes, Obesity, Hyperlipidemia, Antioxidant